ANALISIS PRAKTIK JAMINAN PERSONAL DI BMT (BAITUL MAAL WATTAMWIL) - Ahmad Mufarrihun (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
Abstract: Baitul maal wattamwil (BMT) is one of supporting the economic activities of small communities based on shari'ah. To improve the quality and quantity of service to the community, BMT has a financing product with the requirements of the prospective borrower (customer) must provide collateral. Guarantee or borgtocht is a separate contract type among other contracts. And “borg” should be distinguished from